Homofobia internalizada e cultura militarista: a dualidade entre existência e repressão da sexualidade - Ribeiro, Josivan Alves (2023)
This research has as its birth the life story of openly gay military police officers, who face the challenge of dealing with internalized homophobia in their daily work. The purpose of this work is to develop the practices of homophobia experienced by both the author and the research collaborators within the barracks. The work methodology developed here is based on autoethnography as a means of scrutinizing and bringing the referred stories, based on the constructions of Adams, Bochner and Ellis (2011). As specific objectives, I list the following: to develop internalized homophobia in the military; analyze the narratives of the research subjects in relation to the object of study and, finally, highlight the survival strategies of the interlocutors within the corporation. With regard to questions about gender and sexual orientation, I focused on Butler's readings (2003); With regard to the devices of sexuality and control, I base myself on the readings of Foucault (1988); with regard to the concept of internalized homophobia, I used the Antunes9s constructions (2017). The methodology presented here helped us to obtain data for the research based on self-ethnography, through the speeches of the ways of research and the researcher himself, in a process of rescuing stories and remembering facts and events. Thus, through semi-structured interviews, we obtained data that, when analyzed from the perspective of the theoretical methods used, we came to the conclusion that the results of the research now carried out show us that existing sexualities in the military environment are put to the test, insofar as they have passed the increase in repression filed by subjects who oscillate between compulsory heterosexuality and heteroromantic bisexuality. However, the subjects who come out of the closet end up being victims of this subjection.